A Review of Transparent Insulation Material (TIM) for building energy saving and daylight comfort. (15th September 2018) - Sun, Yanyi; Wilson, Robin; Wu, Yupeng
Highlights: Transparent Insulation Materials offer the potential to improve building performance. State-of-the-art review on methods to characterise Transparent Insulation Materials. Review of methods used to comprehensive evaluate TIMs for building application. Abstract: Improving the energy efficiency of buildings is a key strategy in responding to climate change and resource challenges associated with the use of fossil fuel derived energy. The characteristics of the building envelope play a decisive role in determining building operation energy. Transparent Insulation Materials (TIMs) add to the strategies that may be used to sustain these improvements: they can reduce heat loss by providing high thermal resistance while effectively transmitting solar energy and contributing to the luminous environment. In this review, key types of TIMs and their characterisation in terms of both thermal and optical behaviours are introduced as well as the benefits that may be realised through their application to buildings. Relatively few studies exist regarding the performance of window systems incorporating TIMs. To provide a clear picture of how to accurately predict the performance of TIM integrated window systems, this paper also explores the literature around window systems incorporating complex interstitial structures, as these share many of the same characteristics as TIMs. The experimental and numerical methods used to evaluate the thermal and optical characteristics of complex window systems are summarised and this body of research provides potential methods for tackling similar questions posed in relation to the performance of window systems with TIMs. Finally, this review introduces a method that permits the prediction of the combined thermal and daylight behaviour of spaces served by TIM integrated window systems. The results from using this methodology show that using TIMs over a conventional window system offers a range of benefits to the occupants of buildings. Thus, this review offers a workflow that may be used to assess and analyse the benefit of applying TIMs for building energy saving and daylight comfort in buildings subjected to varying climate conditions.